Model Kepemimpiman dalam Merespon Visi - Asri, Wiyana; Aulan, Zema Yuliana; Hakim, Lukman; Badrun (Mataram University, 2026)
The vision of education serves as a strategic direction that determines the success of institutions in facing global challenges, technological advancements, and social change. The purpose of this study is to analyze leadership models that are effective in formulating and responding to educational visions, to explain the implementation of these leadership models within the stages of strategic management, and to identify supporting and inhibiting factors that influence the successful realization of educational visions. This research employs a literature review method by examining various theories and relevant previous studies. The findings indicate that the most relevant and effective leadership models are visionary leadership which plays a key role in formulating long-term visions and strategic directions and transformational leadership, which is crucial in implementing strategies through motivation, innovation, and the empowerment of human resources. Strategy evaluation requires competencies in strategic thinking, strategic acting, and strategic influencing to ensure that the vision remains aligned with contemporary developments. Supporting factors such as effective communication, collaboration, innovative culture, and staff competence strengthen strategic success, whereas barriers such as resistance to change, limited resources, and weak organizational trust serve as obstacles.